Resilient teachers in precarious contexts: case studies in Spain - Sousa, Carolina Silva (2016)
The article focuses on teachers who face major challenges in very poor socioeconomic and cultural contexts in the Province of Granada, Spain, in which students present many differences in their needs and educational aspirations. The teacher of these schools end up acting in a more social and moral perspetive than academic and the families show little participation and interest among the educational institutions where their children study. The answers obtained from the data collection are unique to each social and educational context and it would be wrong to extrapolate them from one center to another, because each center has its own reality. Despite the high involvement of teachers for the success of their schools.